Characteristics of Students’ Metacognition Process At Informal Deduction Thinking Level in Geometry Problems - Rofii, Ahmad; Sunardi, Sunardi; Irvan, Muhtadi (Universitas Ahmad Dahlan, 2018)
This study aims to determine the characteristics of students’ metacognition process at the level of informal deduction thinking in solving geometry problems. This research is a qualitative descriptive research. 66 elementary students were tested about their thinking ability of Van Hiele geometry by dividing them into some groups according to their geometry thinking level. The informal deductive thinking level group was tested for problem-solving geometry. Furthermore, interviews were conducted to explore the characteristics of their metacognition process. Based on the data analysis, the characteristics sequence of the metacognition process is complete through the process of planning, monitoring, and evaluation. The metacognition process indicator appears in each problem-solving component, from understanding the problem, preparing a problem-solving plan, implementing a problem-solving plan to check the solutions obtained.